Mind-wandering: mechanistic insights from lesion, tDCS, and iEEG. Issue 3 (March 2022) - Kam, Julia W.Y.; Mittner, Matthias; Knight, Robert T.
Abstract : Cognitive neuroscience has witnessed a surge of interest in investigating the neural correlates of the mind when it drifts away from an ongoing task and the external environment. To that end, functional neuroimaging research has consistently implicated the default mode network (DMN) and frontoparietal control network (FPCN) in mind-wandering. Yet, it remains unknown which subregions within these networks are necessary and how they facilitate mind-wandering. In this review, we synthesize evidence from lesion, transcranial direct current stimulation (tDCS), and intracranial electroencephalogram (iEEG) studies demonstrating the causal relevance of brain regions, and providing insights into the neuronal mechanism underlying mind-wandering. We propose that the integration of complementary approaches is the optimal strategy to establish a comprehensive understanding of the neural basis of mind-wandering. Highlights: fMRI evidence has convincingly implicated the default mode network (DMN) and frontoparietal control network (FPCN) in mind-wandering. Less is known about which subregions in these networks are necessary, and how they facilitate mind-wandering. A growing number of studies use the lesion and transcranial direct current stimulation (tDCS) approaches to establish the causal link between DMN and FPCN subregions and mind-wandering. They have also identified the mechanistic role of intra-DMN connectivity in this phenomenon. Intracranial EEG studies have revealed the neurophysiological mechanism underlying mind-wandering and its preferred frequencies in the theta and high-frequency band for communication within and across large-scale neural networks. To achieve an in-depth understanding of the where, when, and how mind-wandering is implemented in the brain requires a shift away from the predominant reliance on one method toward an integration of complementary methodological approaches.